Diversification as a Way of Increasing the Sustainability of the Azerbaijan Economy - M. Guliyev (Евразийская интеграция: экономика, право, политика, 2019)
Falling of the world oil prices exposed the existing problems of oil-producing countries and emerging insecurity of their economies. Diversification is a modern callenge for the oil-producing countries of the CIS. World economic practices have repeatedly proved that the diversified economy possesses the highest degree of stability. Increased attention to diversification is one of the main directions of economic policy of Azerbaijan today.